2021
DOI: 10.18280/i2m.200308
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation to Determine the Concentration of Radon in Cosmetics Using a Nuclear Track Detector (CR-39)

Abstract: The nuclear track detector CR-39 is used in the detection of radon gas concentration in selected samples of cosmetics in the local market. Products of wide use are selected and employed in the current study. Six types of cosmetic products of different origins are tested by taking equivalent quantities of these products and putting them in plastic boxes. The detector is left with the samples for a period of 50 days. In addition to measuring the rate of surface evaporation of radon gas, measurements of the annua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Conclusion: from the results of the study, it can be concluded that the face scrub preparation of activated charcoal coffee grounds (Coffea arabica L.) with a concentration of 3 % and vitamin E 5 % is a formula that meets the evaluation of the preparation and measures the effectiveness of anti-ageing Keywords: activated coffee charcoal (charcoal), face scrub formulation, anti-ageing, vitamin E and have better skin cleansing power than preparations without activated charcoal [7]. Activated charcoal as an adsorbent is very good if used in an exfoliant preparation such as scrubs and scrubs so that the skin regeneration process will also be better and can avoid the effects of premature ageing [8].…”
Section: Test Anti-aging Activity In a Face Scrub Preparation That Co...mentioning
confidence: 99%
“…Conclusion: from the results of the study, it can be concluded that the face scrub preparation of activated charcoal coffee grounds (Coffea arabica L.) with a concentration of 3 % and vitamin E 5 % is a formula that meets the evaluation of the preparation and measures the effectiveness of anti-ageing Keywords: activated coffee charcoal (charcoal), face scrub formulation, anti-ageing, vitamin E and have better skin cleansing power than preparations without activated charcoal [7]. Activated charcoal as an adsorbent is very good if used in an exfoliant preparation such as scrubs and scrubs so that the skin regeneration process will also be better and can avoid the effects of premature ageing [8].…”
Section: Test Anti-aging Activity In a Face Scrub Preparation That Co...mentioning
confidence: 99%